Arab women: No longer silent, but can they guarantee rights for themselves - Sayed, Sana (2012)
Civil unrest in the Arab world has lead to seismic political, social, and economic changes in countries such as Egypt, Libya, Syria, Tunisia, Bahrain, and now Yemen. While the changes that are being undertaken in these countries is and will be an ongoing process, it is undeniable that Arab women have been at the forefront of both the protests and dialogue that seek to provide social change. When women engage in politics and make their voices heard they not only enact change within their own nations, but also motivate women in neighboring regions to create a platform on which their issues can be voiced. Women in Saudi Arabia, for example, have successfully achieved some social change based on what is happening in neighboring countries. In an attempt to avoid civil unrest in his own nation, "King Abdullah bin Abd al-Aziz has announced that women will be able to participate in municipal elections in 2015. He also announced that women may become full voting members of the consultative Shura council" (Khalife, 2011). The role of Arab women in their respective societies continues to be shaped by the cultural and political climate in which they exist. This research-based essay will begin with a brief highlight of how women have participated in the major events that recently unfolded in the Arab world. I will then discuss how political upheaval in the Arab region demonstrates a greater need for women/gender recognition and study. The following questions will be addressed: To what extent does political mobilization ensure changes in Arab women's socio-political status? What strategies can women active in protest movements pursue to increase the likelihood that they actually achieve full citizenship? How will economic austerity programs affect women's struggles for their rights? And finally, how do the dynamic and varying characteristics of Arab women complicate our notions of freedom?